Epidemiological Evolution of Congenital Syphilis in the State of Sergipe in a Decade (Research, Society and Development, 2022)
Congenital syphilis results from the hematogenous spread of Treponema pallidum from an infected pregnant woman who is untreated or inadequately treated for her fetus, usually transplacentally, regardless of gestational age. Therefore, this study aims to analyze the temporal dynamics according to epidemiological data of congenital syphilis in primary health care between 2011 and 2020 in the State of Sergipe, as well as to evaluate maternal sociodemographic variables of children diagnosed with congenital syphilis in the last decade . Data were collected using databases from the Ministry of Health (DATASUS) and IBGE, being compiled into spreadsheets in the Microsoft Office Excel program and evaluated by calculating absolute and relative frequencies, in addition to the standard deviation of the variables addressed. The amount of data shows that there were a total of 3,675 reported cases of congenital syphilis in the State of Sergipe between 2011 and 2020, being more prevalent in children of mixed-race mothers, with incomplete elementary education and prenatal care during pregnancy. Furthermore, the notification rates of congenital syphilis are higher in the eastern region of the State of Sergipe. After analyzing this work, it is clear that the state of Sergipe, despite being the third-to-last state in the northeast on a decreasing scale in terms of the number of cases of congenital syphilis in the last decade, presents similarity in the maternal variables studied and the concept of the concept itself, according to the literature. It is necessary to train health professionals for the management of the disease and effective public policies on the social determinants of congenital syphilis.